Dramaturgia da imagem : potências e ativações em cena - Horevicht, Tatiana Mendes (2024)
How is image dramaturgy presented in contemporary theater? This research discusses the power of scenic images as activators of an image dramaturgy. For the discussion I use the understanding of image dramaturgy, organic and mechanical model, proposed by José Sànchez (2002), observing the scenic productions that I followed between the years 2021 and 2022, namely, A Divina Comédia | Paraíso (2022), by Teatro O Bando, and Thebes at the time of yellow fever (2022), by Odin Teatret. In addition, I check how the dramaturgy of image is presented in my theatrical production in the shows Cidade dos Outros (2010), Criame (2018), and EntreNãoLugares (2019). To create a path for debate, I organized, as an approach strategy, three clues for observing the potential of image dramaturgy in the chosen works, which I name as: activation of memory, activation of the virtual, and activation of the imaginary. To construct the tracks, Henri Bergson's (2006) notions of memory, Gilles Deleuze and Felix Guattari's (2012) notions of becoming, and the notion of imaginary developed by Gilbert Durand (1997) were used. As this is research into the arts, I use cartography designed by Deleuze and Guattari (1986), and developed by Suely Rolnik (1989), as a methodological investigation procedure. The investigation path was supported by notebooks and other residual records of the works listed, seeking to identify how, in contemporary theater, powerful scenic images construct a dramaturgy of images.